Post-stack seismic inversion in reservoir quality assessment: petrophysical aspects of acoustic impedance - Gyasi, Emmanuel Kobina (My University, 2025)
The Morrison Northeast field produces hydrocarbon from the thin Viola formation: Among the 12 wells that have been drilled into the Viola formation, five of them have proven to be non-producing. This problem of well placement is caused in part by complex seismic amplitude responses arising from both the constructive and destructive interference reflectors waveform (tuning effects) and petrophysical and diagenetic reservoir rock heterogeneities. It is therefore consequential to understand acoustic impedance variation in relation to well-logs petrophysical analysis, to guide placement of new wells and/or enhanced oil recovery programs. This study illuminates the utility of acoustic impedance rock property in mapping the variation of reservoir porosity and facies. It is noteworthy that acoustic impedance is independent of stratigraphic thickness and is strongly dependent on porosity variations within the Viola carbonates. Significant correlations of impedance to porosity for leverage well placement planning in the development of Morrison Field. This study has also provided insights on needed seismic phase adjustments (+70) for more accurate time-to-depth conversion of the Viola-Top seismic horizon. The 3D seismic data has undergone spectral whitening to boost the seismic resolution by broadening the spectral bandwidth and flattening the amplitude spectrum. Seismic horizons were retracked, a synthetic to seismic well ties were established, a representative wavelet was derived to improve inversion accuracy, and an inverted acoustic impedance log was obtained at well locations. Finally, beyond conventional inversion techniques, this study presents data driven machine learning approaches to predict impedance values in areas lacking well control. Providing a robust framework for improving hydrocarbon exploration and production efficiency. The significance of this workflow lies in establishing a workflow that enhances the reservoir quality assessment, offering practical solutions for optimizing well placement and maximizing hydrocarbon recovery in complex geological settings based on acoustic impedance-reservoir porosity relationships and improved accuracy of time-to-depth conversion.
Keywords: Acoustic impedance; Seismic inversion; Spectral enhancement; Post-stack; Viola; Reservoir